THERMAL PROPERTIES AND ACTIVATION ENERGY OF THE [Zr0.645Ni0.155Al0.115Cu0.085]98Si2 AMORPHOUS ALLOY - Iqbal, M.; Akhter, J. I.; Hu, Z. Q. (The Nucleus, 2010)
Zr-based amorphous alloys are novel materials having wide range of applications. Melt spun amorphous ribbon with composition (Zr0.645Ni0.155Al0.115Cu0.085)98Si2 of 50 Âµm thickness was synthesized to investigate the thermal properties and activation energy. Differential scanning calorimetry (DSC) was used to investigate these properties. X-ray diffraction (XRD) and scanning electron microscopy (SEM) were employed for phase analysis and microstructural study. Thermal parameters were derived from DSC measurements. Phases like NiZr2, CuZr2 and SiZr2 were identified in the samples annealed at various temperatures. It was found that Si addition had positive effect on most of the thermal parameters.